Kansas survey: What do commercial cow-calf producers consider when buying herd sires? - Bolze, R.; Lambert, C.; O'Neill, S.; Corah, L. (Kansas State University. Agricultural Experiment Station, 2011)
Recently, Kansas State University surveyed the factors a commercial cowman considers when he buys Angus, Simmental, or Hereford bulls. A mail survey of the customers of 29 purebred breeders of those three breeds was conducted. We attempted to include a reasonable cross section of both performance and show-ring-oriented breeders. A total of 1,447 survey forms were distributed and 613 (42%) were returned.
Keywords: Beef; Commerical cow-calf producers; Herd sires